Asphalt-based hard carbon microspheres, preparation method thereof and sodium ion battery
By combining asphalt with alkaline zinc carbonate microspheres and metal salt-based modifiers, modified asphalt-based hard carbon microspheres are formed, solving the problem of low sodium ion battery capacity of asphalt-based carbon material and achieving high ratio The surface area and rich pore structure improve electrochemical performance and provide excellent performance for the negative electrode materials of sodium ion battery.
Patent Information
- Application Number
- CN202411403308.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-07
AI Technical Summary
The existing asphalt-based carbon materials have low capacity, resulting in poor sodium storage performance in sodium ion batteries.
By stirring and reacting asphalt with alkali zinc carbonate microspheres in a solvent, asphalt-based carbon microspheres are formed, then mixed with metal salt modifiers, annealing and carbonization, and finally pickling and water washing are carried out to obtain the modified Asphalt-based hard charcoal microspheres. This method increases the filling and insertion of sodium ions by hindering the orderly arrangement of molecules of asphalt during high-temperature pyrolysis and carbonization.
It significantly improves the platform area capacity of bituminous sodium ion batteries, improves the specific surface area and pore structure of the material, enhances the electrochemical performance, and makes hard charcoal materials have high discharge capacity, good charging and discharge efficiency and cycling performance, suitable for sodium Ion battery negative electrode material.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of material preparation, and in particular relates to a metal salt-modified asphalt-based hard carbon microsphere, a preparation method thereof, and a sodium ion battery. Background Art
[0002] With the massive consumption of fossil energy, while achieving the rational and effective utilization of limited resources, energy conservation and the development of renewable energy have become research hotspots. In the development and utilization of renewable energy, carbon materials play a vital role because they can be widely used as electrode materials or energy storage systems. In principle, carbon materials can be prepared from various carbon-containing sources. Generally, people tend to choose low-cost precursors such as biomass, polymers and asphalt to produce various carbon materials. my country has abundant coal resources and ranks first in the world in coking capacity. The yield of coal tar pitch (CTP) in the coking industry is about 50% to 60%. At present, asphalt is mainly used in traditional fields such as adhesives, anti-corrosion, waterproofing, and road construction materials due to its good corrosion resistance and adhesion. However, the above traditional applications can only convert asphalt into low-value-added products. Therefore, it is urgent to explore and develop new applications to convert asphalt into high-value products. It is worth noting that asphalt has the advantages of high carbon content, abundant resources and low price, and is considered to be the most potential candidate for the production of carbon materials. At present, since asphalt is easier to graphitize than biomass and synthetic polymers, the preparation of energy storage carbon materials has become an important way to deeply utilize asphalt. Currently, various carbon materials such as carbon spheres, wires, sheets, and networks have been prepared from pitch, and they have been widely evaluated as electrode materials for supercapacitors (SCs), lithium-ion, sodium-ion, and potassium-ion batteries.
[0003] In the research of sodium ion battery electrode materials, asphalt has the advantages of high carbon yield, environmental friendliness, and low cost. It is an ideal carbon source for preparing sodium ion battery negative electrode materials, but its specific capacity is low, about 80 mAh / g. If its sodium storage performance is improved, asphalt will be an excellent sodium ion battery negative electrode material. The low sodium storage capacity of asphalt is because the molecules of asphalt undergo orderly rearrangement to form a graphite-like layer structure during the high-temperature pyrolysis and carbonization process, which is not conducive to the storage of sodium ions. Summary of the invention
[0004] In order to solve the problem of low sodium capacity of pitch-based carbon materials in the above-mentioned prior art, the present invention provides a pitch-based hard carbon microsphere and a preparation method thereof and a sodium ion battery.
[0005] The present invention is achieved through the following technical solutions: A method for preparing pitch-based hard carbon microspheres comprises the following steps: S1, stirring asphalt and basic zinc carbonate microspheres in a solvent to react, and drying the obtained solid product to obtain an asphalt-based carbon microsphere precursor; S2, mixing the asphalt-based carbon microsphere precursor with a metal salt modifier to obtain a modified asphalt-based carbon microsphere precursor; the metal salt modifier is a zinc salt, a magnesium salt or a calcium salt; S3, annealing and carbonizing the modified pitch-based carbon microsphere precursor; S4, acid-washing, water-washing and drying the carbonized product to obtain asphalt-based hard carbon microspheres.
[0006] Preferably, in S1, the preparation method of the basic zinc carbonate microspheres is: adding zinc nitrate hexahydrate and urea to water, carrying out a hydrothermal reaction, and washing and drying the product to obtain basic zinc carbonate microspheres.
[0007] Preferably, S1 specifically comprises: adding asphalt and basic zinc carbonate microspheres into a solvent, stirring at room temperature, and then separating the solid and liquid, and drying the solid product to obtain a asphalt-based carbon microsphere precursor.
[0008] Preferably, in S1, the mass ratio of basic zinc carbonate microspheres to asphalt is (1-10):1.
[0009] Preferably, in S2, the zinc salt is one or more of zinc propionate, zinc gluconate, zinc acetate, zinc oxalate, zinc citrate, zinc lactate, zinc phytate, zinc formate, zinc sulfate, zinc octanoate, zinc isooctanoate and zinc laurate; the magnesium salt is one or more of magnesium propionate, magnesium gluconate, magnesium acetate, magnesium oxalate, magnesium citrate, magnesium lactate, magnesium phytate, magnesium formate, magnesium sulfate, magnesium octanoate, magnesium isooctanoate and magnesium laurate; the calcium salt is one or more of calcium propionate, calcium gluconate, calcium acetate, calcium oxalate, calcium citrate, calcium lactate, calcium phytate, calcium formate, calcium sulfate, calcium octanoate, calcium isooctanoate and calcium laurate.
[0010] Preferably, in S2, the ratio of the asphalt-based carbon microsphere precursor to the metal salt modifier is 1:(1-5).
[0011] Preferably, in S3, the annealing temperature is 100-500° C., and the annealing time is 1-12 hours.
[0012] Preferably, in S3, the carbonization temperature is 800-1600° C., and the carbonization time is 1-12 h.
[0013] The present invention also provides a pitch-based hard carbon microsphere obtained by the preparation method as described above.
[0014] The present invention also provides a sodium ion battery, comprising a negative electrode, wherein the negative electrode comprises the asphalt-based hard carbon microspheres as described above.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The preparation method of asphalt-based hard carbon microspheres of the present invention, by adding metal salt modifiers to hinder the orderly arrangement of asphalt molecules during high-temperature pyrolysis carbonization, promote the formation of closed pores, and limit the graphitization of asphalt during high-temperature carbonization, thereby obtaining a hard carbon material. The metal salt modifiers are pyrolyzed to produce gaseous carbon oxides and solid products. The gaseous carbon oxides consume excess hydrogen to prevent the orderly arrangement of the carbon skeleton, and the solid products expand the interlayer spacing. Finally, after removing the metal oxide nanoparticles, a large number of closed pores are introduced into the carbon material, which effectively increases the filling of sodium ions in the closed pores of the carbon material and the insertion amount in the carbon layer, and increases the platform area capacity of the asphalt-based sodium ion battery. In addition, the use of basic zinc carbonate microspheres as a template to form microspheres of asphalt is effective in improving the specific surface area of the material, enriching the surface structure, and effectively improving its electrochemical performance compared to direct modification of unballed asphalt; Compared with other templates, the use of basic zinc carbonate microspheres as a template can play multiple roles such as template assistance, oxidizing gases generated by pyrolysis to prevent asphalt graphitization, small molecular gases generated during pyrolysis, and zinc oxide solids generated after pyrolysis to regulate the closed-pore structure. The present invention improves the pore structure and morphology of the hard carbon material through the combined action of the template method and the metal salt modifier, so that the hard carbon material has a high specific surface area and a rich pore structure. The obtained hard carbon material has excellent performance, high discharge capacity and initial charge and discharge efficiency, and good large current charge and discharge performance; good cycle performance, good safety, good adaptability to electrolytes and other additives, stable product properties, and almost no difference between batches. It can be used as a negative electrode material for sodium ion batteries, providing a new way for the high-value utilization of asphalt. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0017] Figure 1 This is a scanning electron microscope image of the pitch-based hard carbon microspheres prepared in Example 1.
[0018] Figure 2 This is the nitrogen adsorption-desorption curve of the pitch-based hard carbon microspheres prepared in Example 1.
[0019] Figure 3 These are the initial charge and discharge diagrams of the pitch-based hard carbon microspheres prepared in Examples 1, 4, and 5.
[0020] Figure 4 This is the efficiency diagram of the pitch-based hard carbon microspheres prepared in Examples 1, 4, and 5. DETAILED DESCRIPTION
[0021] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0022] It should be noted that the process equipment or devices not specifically specified in the following embodiments are all conventional equipment or devices in the art.
[0023] It should be noted that the terms "include" and "have" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to define the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.
[0024] In the present invention, the disclosure of numerical ranges includes all values within the entire range and the disclosure of further subdivided ranges, including the endpoints and sub-ranges given for these ranges.
[0025] In the present invention, the raw materials, equipment, etc. involved, unless otherwise specified, are all raw materials and equipment that can be made through commercial channels or known methods; the methods involved, unless otherwise specified, are all conventional methods.
[0026] The method for preparing the metal salt-modified asphalt-based hard carbon microspheres of the embodiment of the present invention comprises the following steps: S1. Synthesize basic zinc carbonate template for the subsequent preparation of asphalt-based carbon microspheres.
[0027] In the embodiments of the present invention, the purpose of synthesizing the basic zinc carbonate template is to be used for the preparation of asphalt-based carbon microspheres and to change the structure and morphology of the asphalt material.
[0028] In some embodiments, the template is synthesized by dissolving zinc nitrate hexahydrate and urea in deionized water under ultrasonic stirring, transferring the solution to a stainless steel autoclave lined with polytetrafluoroethylene, and heating at 100°C for 8 to 12 hours. After cooling to room temperature, the white precipitate is washed several times with pure water and ethanol, and then dried at 80 to 100°C for 6 to 24 hours. The mass ratio of zinc nitrate hexahydrate to urea is 1:2, and the concentration of the zinc nitrate hexahydrate solution is 0.05 to 0.5M.
[0029] S2. Using the basic zinc carbonate template obtained in step S1, a pitch-based carbon microsphere precursor is prepared.
[0030] In some embodiments, the preparation conditions of the asphalt-based carbon microspheres are as follows: basic zinc carbonate microspheres, asphalt and tetrahydrofuran are stirred at room temperature in a fume hood, and then solid-liquid separation is performed, and the obtained solid is dried at 40-75°C for 6-12 hours, the mass ratio of basic zinc carbonate microspheres to asphalt is (1-10):1, the amount of tetrahydrofuran added is 15-50 mL per 1 g of asphalt, and the asphalt used is high-temperature coal asphalt or extra-high temperature coal asphalt (CTP), and the asphalt is extra-high temperature coal asphalt. Preferably, a 300-350 mesh vibrating sieving machine is used to sieve the coal asphalt.
[0031] The ultra-high temperature coal tar pitch described in the present invention refers to a coal tar pitch having a softening point of 200°C to 280°C. The high temperature coal tar pitch refers to a coal tar pitch having a softening point of 100°C to 200°C.
[0032] S3. Adding a metal salt modifier to the asphalt-based carbon microsphere precursor to obtain a modified asphalt-based carbon microsphere precursor.
[0033] In some embodiments, the metal salt modifier is a zinc salt, a magnesium salt or a calcium salt; the zinc salt is one or more of zinc propionate, zinc gluconate, zinc acetate, zinc oxalate, zinc citrate, zinc lactate, zinc phytate, zinc formate, zinc sulfate, zinc octanoate, zinc isooctanoate and zinc laurate; the magnesium salt is one or more of magnesium propionate, magnesium gluconate, magnesium acetate, magnesium oxalate, magnesium citrate, magnesium lactate, magnesium phytate, magnesium formate, magnesium sulfate, magnesium octanoate, magnesium isooctanoate and magnesium laurate; the calcium salt is one or more of calcium propionate, calcium gluconate, calcium acetate, calcium oxalate, calcium citrate, calcium lactate, calcium phytate, calcium formate, calcium sulfate, calcium octanoate, calcium isooctanoate and calcium laurate.
[0034] In some embodiments, two metal salt modifiers are added at a mass ratio of 1:(1-5), or three metal salt modifiers are added at a mass ratio of 1:1:1, 5:2.5:2.5, or 8:1:1.
[0035] S4, subjecting the modified asphalt-based carbon microsphere precursor to a low-temperature annealing treatment in an inert atmosphere, a high-temperature carbonization treatment, and then acid washing, water washing, and drying treatment to obtain metal salt modified asphalt-based carbon microspheres.
[0036] In the embodiments of the present invention, the purpose of performing low-temperature annealing and high-temperature carbonization is to thermally decompose the modifier and fully carbonize the material.
[0037] In some embodiments, during the low temperature annealing process and the high temperature annealing process, the inert atmosphere includes but is not limited to at least one of nitrogen, argon, and helium.
[0038] In some embodiments, the inert gas flow rate is 10 to 80 mL / min, including but not limited to 10 mL / min, 20 mL / min, 30 mL / min, 40 mL / min, 50 mL / min, 60 mL / min, 70 mL / min, and 80 mL / min. The inert gas flow rate can be adjusted within the above range.
[0039] In some embodiments, during the low temperature annealing treatment and the high temperature annealing treatment, the heating rate is 2-5°C / min, including but not limited to 2°C / min, 3°C / min, and 5°C / min.
[0040] In some embodiments, the temperature of the low temperature annealing treatment is 100-500° C., including but not limited to 100° C., 200° C., 300° C., 400° C., and 500° C.; In some embodiments, the low temperature annealing time is 1 to 12 hours, including but not limited to 2 hours, 4 hours, 6 hours, 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 22 hours, and 24 hours.
[0041] In some embodiments, the high temperature carbonization treatment time is 1 to 12 hours, including but not limited to 2 hours, 4 hours, 6 hours, 8 hours, 10 hours, and 12 hours.
[0042] In some embodiments, the high temperature carbonization treatment temperature is 800-1600°C, including but not limited to 800°C, 1000°C, 1200°C, 1400°C, and 1600°C.
[0043] In some embodiments, the acid washing is to repeatedly wash the sample with a 0.1-3M acid solution to remove oxides and inorganic salts formed by the metal salt modifier, including but not limited to 0.1M, 0.5M, 1M, 2M, and 3M.
[0044] In some embodiments, the pickling uses at least one of hydrochloric acid, sulfuric acid, and nitric acid.
[0045] In some embodiments, the water washing is performed by filtering with deionized water for several times until the water becomes neutral.
[0046] In some embodiments, the drying condition is drying at 80-100° C. for 6-24 hours to obtain the final sample.
[0047] In some embodiments, low-temperature annealing and high-temperature carbonization are performed in an inert atmosphere furnace, a tubular furnace, or the like.
[0048] The asphalt-based carbon microspheres prepared in the embodiment of the present invention have a high specific surface area and a rich pore structure. The ordered arrangement of asphalt molecules at high temperature and the formation of closed pores are changed by modification with metal salts, thereby obtaining a hard carbon material. The hard carbon material obtained by this method has excellent performance, high discharge capacity and initial charge and discharge efficiency, good large current charge and discharge performance, good cycle performance, and good safety. It has good adaptability to electrolytes and other additives, stable product properties, and almost no difference between batches. It can be used as a negative electrode material for sodium ion batteries, providing a new way to high-value utilization of asphalt. And low cost of raw materials and other characteristics.
[0049] In some embodiments, the specific surface area of the pitch-based carbon microspheres is 1000 to 1800 m 2 / g, and the average pore size is 1.9~3.3nm.
[0050] As a non-limiting example, the pitch-based carbon microspheres have a specific surface area of 1000 m 2 / g、1200m 2 / g、1400m 2 / g、1600m 2 / g、1800m 2 / g, etc.
[0051] As non-limiting examples, the pore diameter of the pitch-based carbon microspheres is 1.8 nm, 2.2 nm, 2.4 nm, 3 nm, or 3.1 nm, etc.
[0052] The pitch-based carbon microspheres of the present invention can be widely used in fields such as energy storage, and in particular in the field of negative electrode materials for sodium ion batteries.
[0053] The sodium ion battery negative electrode of the embodiment of the present invention includes the asphalt-based hard carbon microspheres of the embodiment of the present invention.
[0054] Certain features of the present technology are further illustrated in the following non-limiting examples.
[0055] Example 1 A method for preparing metal salt-modified asphalt-based hard carbon microspheres comprises the following steps: (1) Zn5(OH)6(CO3)2 microspheres were synthesized by hydrothermal method. Briefly, 1.8 g zinc nitrate hexahydrate and 3.6 g urea were dissolved in 30 mL deionized water (the concentration of zinc nitrate hexahydrate solution was 0.2 M) under ultrasonic stirring. Then, the solution was transferred to a 45 mL polytetrafluoroethylene-lined stainless steel autoclave and heated at 100 °C for 8 h. After cooling to room temperature, the white precipitate was washed several times with pure water and ethanol, and then dried at 80 °C overnight.
[0056] (2) 2.0 g Zn5(OH)6(CO3)2 microspheres, 0.4 g CTP and 10 mL tetrahydrofuran were stirred at room temperature in a fume hood. The solid product obtained by filtration was dried at 40 °C for 12 h.
[0057] (3) 0.4 g of zinc gluconate was mechanically mixed into the obtained dry sample, and then the obtained mixture was annealed at 400 °C for 2 h at a N2 flow rate of 60 mL / min and a heating rate of 5 °C / min, and then carbonized at 1200 °C for 2 h at a heating rate of 5 °C / min.
[0058] (4) The sample was repeatedly washed with 1 M HCl solution to remove ZnO and inorganic salts, subsequently washed with deionized water several times until neutral, and dried at 100 °C for 12 h to obtain the final sample.
[0059] Example 2 A method for preparing metal salt-modified asphalt-based hard carbon microspheres comprises the following steps: (1) Zn5(OH)6(CO3)2 microspheres were synthesized by hydrothermal method. Briefly, 1.8 g zinc nitrate hexahydrate and 3.6 g urea were dissolved in 30 mL deionized water (the concentration of zinc nitrate hexahydrate solution was 0.2 M) under ultrasonic stirring. Then, the solution was transferred to a 45 mL polytetrafluoroethylene-lined stainless steel autoclave and heated at 100 °C for 8 h. After cooling to room temperature, the white precipitate was washed several times with pure water and ethanol, and then dried at 80 °C overnight.
[0060] (2) 2.0 g Zn5(OH)6(CO3)2 microspheres, 0.4 g CTP and 10 mL tetrahydrofuran were stirred at room temperature in a fume hood. The solid product obtained by filtration was dried at 40 °C for 12 h.
[0061] (3) 0.4 g of zinc gluconate was mechanically mixed in the dry sample, and the obtained mixture was then annealed at 400 °C for 2 h at a N2 flow rate of 60 mL / min and a heating rate of 5 °C / min, followed by carbonization at 1200 °C for 2 h at a heating rate of 5 °C / min.
[0062] (4) The sample was repeatedly washed with 1 M HCl solution to remove ZnO and inorganic salts, subsequently washed with deionized water several times until neutral, and dried at 100 °C for 12 h to obtain the final sample.
[0063] Example 3 A method for preparing metal salt-modified asphalt-based hard carbon microspheres comprises the following steps: (1) Zn5(OH)6(CO3)2 microspheres were synthesized by hydrothermal method. Briefly, 1.8 g zinc nitrate hexahydrate and 3.6 g urea were dissolved in 30 mL deionized water (the concentration of zinc nitrate hexahydrate solution was 0.2 M) under ultrasonic stirring. Then, the solution was transferred to a 45 mL polytetrafluoroethylene-lined stainless steel autoclave and heated at 100 °C for 8 h. After cooling to room temperature, the white precipitate was washed several times with pure water and ethanol, and then dried at 80 °C overnight.
[0064] (2) 2.0 g Zn5(OH)6(CO3)2 microspheres, 0.5 g CTP and 10 mL tetrahydrofuran were stirred at room temperature in a fume hood. The solid product obtained by filtration was dried at 40 °C for 12 h.
[0065] (3) 0.4 g of zinc gluconate was mechanically mixed in the dry sample, and the obtained mixture was then annealed at 400 °C for 2 h at a N2 flow rate of 60 mL / min and a heating rate of 5 °C / min, followed by carbonization at 1200 °C for 2 h at a heating rate of 5 °C / min.
[0066] (4) The sample was repeatedly washed with 1 M HCl solution to remove ZnO and inorganic salts, subsequently washed with deionized water several times until neutral, and dried at 100 °C for 12 h to obtain the final sample.
[0067] Example 4 A method for preparing metal salt-modified asphalt-based hard carbon microspheres comprises the following steps: (1) Zn5(OH)6(CO3)2 microspheres were synthesized by hydrothermal method. Briefly, 1.8 g zinc nitrate hexahydrate and 3.6 g urea were dissolved in 30 mL deionized water (the concentration of zinc nitrate hexahydrate solution was 0.2 M) under ultrasonic stirring. Then, the solution was transferred to a 45 mL polytetrafluoroethylene-lined stainless steel autoclave and heated at 100 °C for 8 h. After cooling to room temperature, the white precipitate was washed several times with pure water and ethanol, and then dried at 80 °C overnight.
[0068] (2) 2.0 g Zn5(OH)6(CO3)2 microspheres, 0.4 g CTP and 10 mL tetrahydrofuran were stirred at room temperature in a fume hood. The solid product obtained by filtration was dried at 40 °C for 12 h.
[0069] (3) 0.4 g of zinc citrate was mechanically mixed in the dried sample, and the obtained mixture was then annealed at 400 °C for 2 h at a N2 flow rate of 60 mL / min and a heating rate of 5 °C / min, followed by carbonization at 1200 °C for 2 h at a heating rate of 5 °C / min.
[0070] (4) The sample was repeatedly washed with 1 M HCl solution to remove ZnO and inorganic salts, subsequently washed with deionized water several times until neutral, and dried at 100 °C for 12 h to obtain the final sample.
[0071] Example 5 A method for preparing metal salt-modified asphalt-based hard carbon microspheres comprises the following steps: (1) Zn5(OH)6(CO3)2 microspheres were synthesized by hydrothermal method. Briefly, 1.8 g zinc nitrate hexahydrate and 3.6 g urea were dissolved in 30 mL deionized water (the concentration of zinc nitrate hexahydrate solution was 0.2 M) under ultrasonic stirring. Then, the solution was transferred to a 45 mL polytetrafluoroethylene-lined stainless steel autoclave and heated at 100 °C for 8 h. After cooling to room temperature, the white precipitate was washed several times with pure water and ethanol, and then dried at 80 °C overnight.
[0072] (2) 2.0 g Zn5(OH)6(CO3)2 microspheres, 0.4 g CTP and 10 mL tetrahydrofuran were stirred at room temperature in a fume hood. The solid product obtained by filtration was dried at 40 °C for 12 h.
[0073] (3) 0.4 g of zinc acetate was mechanically mixed in the dry sample, and the obtained mixture was then annealed at 400 °C for 2 h at a N2 flow rate of 60 mL / min and a heating rate of 5 °C / min, followed by carbonization at 1200 °C for 2 h at a heating rate of 5 °C / min.
[0074] (4) The sample was repeatedly washed with 1 M HCl solution to remove ZnO and inorganic salts, subsequently washed with deionized water several times until neutral, and dried at 100 °C for 12 h to obtain the final sample.
[0075] Example 6 A method for preparing metal salt-modified asphalt-based hard carbon microspheres comprises the following steps: (1) Zn5(OH)6(CO3)2 microspheres were synthesized by hydrothermal method. Briefly, 1.8 g zinc nitrate hexahydrate and 3.6 g urea were dissolved in 30 mL deionized water (the concentration of zinc nitrate hexahydrate solution was 0.2 M) under ultrasonic stirring. Then, the solution was transferred to a 45 mL polytetrafluoroethylene-lined stainless steel autoclave and heated at 100 °C for 8 h. After cooling to room temperature, the white precipitate was washed several times with pure water and ethanol, and then dried at 80 °C overnight.
[0076] (2) 2.0 g Zn5(OH)6(CO3)2 microspheres, 0.4 g CTP and 10 mL tetrahydrofuran were stirred at room temperature in a fume hood. The solid product obtained by filtration was dried at 40 °C for 12 h.
[0077] (3) 0.4 g of zinc gluconate and zinc acetate (mass ratio 1:1) were mechanically mixed in the dry sample, and the obtained mixture was then annealed at 400 °C for 2 h at a N2 flow rate of 60 mL / min and a heating rate of 5 °C / min, followed by carbonization at 1200 °C for 2 h at a heating rate of 5 °C / min.
[0078] (4) The sample was repeatedly washed with 1 M HCl solution to remove ZnO and inorganic salts, subsequently washed with deionized water several times until neutral, and dried at 100 °C for 12 h to obtain the final sample.
[0079] Example 7 A method for preparing metal salt-modified asphalt-based hard carbon microspheres comprises the following steps: (1) Zn5(OH)6(CO3)2 microspheres were synthesized by hydrothermal method. Briefly, 1.8 g zinc nitrate hexahydrate and 3.6 g urea were dissolved in 30 mL deionized water (the concentration of zinc nitrate hexahydrate solution was 0.2 M) under ultrasonic stirring. Then, the solution was transferred to a 45 mL polytetrafluoroethylene-lined stainless steel autoclave and heated at 100 °C for 8 h. After cooling to room temperature, the white precipitate was washed several times with pure water and ethanol, and then dried at 80 °C overnight.
[0080] (2) 2.0 g Zn5(OH)6(CO3)2 microspheres, 0.4 g CTP and 10 mL tetrahydrofuran were stirred at room temperature in a fume hood. The solid product obtained by filtration was dried at 40 °C for 12 h.
[0081] (3) 0.4 g of magnesium gluconate was mechanically mixed into the dry sample, and the obtained mixture was then annealed at 400 °C for 2 h at a N2 flow rate of 60 mL / min and a heating rate of 5 °C / min, followed by carbonization at 1200 °C for 2 h at a heating rate of 5 °C / min.
[0082] (4) The sample was repeatedly washed with 1 M HCl solution to remove ZnO and inorganic salts, subsequently washed with deionized water several times until neutral, and dried at 100 °C for 12 h to obtain the final sample.
[0083] Example 8 A method for preparing metal salt-modified asphalt-based hard carbon microspheres comprises the following steps: (1) Zn5(OH)6(CO3)2 microspheres were synthesized by hydrothermal method. Briefly, 1.8 g zinc nitrate hexahydrate and 3.6 g urea were dissolved in 30 mL deionized water (the concentration of zinc nitrate hexahydrate solution was 0.2 M) under ultrasonic stirring. Then, the solution was transferred to a 45 mL polytetrafluoroethylene-lined stainless steel autoclave and heated at 100 °C for 8 h. After cooling to room temperature, the white precipitate was washed several times with pure water and ethanol, and then dried at 80 °C overnight.
[0084] (2) 2.0 g Zn5(OH)6(CO3)2 microspheres, 0.4 g CTP and 10 mL tetrahydrofuran were stirred at room temperature in a fume hood. The solid product obtained by filtration was dried at 40 °C for 12 h.
[0085] (3) 0.4 g of zinc gluconate, zinc acetate, and zinc citrate (mass ratio 1:1:1) were mechanically mixed in the dry sample, and the obtained mixture was then annealed at 400 °C for 2 h at a N2 flow rate of 60 mL / min and a heating rate of 5 °C / min, followed by carbonization at 1200 °C for 2 h at a heating rate of 5 °C / min.
[0086] (4) The sample was repeatedly washed with 1 M HCl solution to remove ZnO and inorganic salts, subsequently washed with deionized water several times until neutral, and dried at 100 °C for 12 h to obtain the final sample.
[0087] Example 9 This embodiment is basically the same as Embodiment 1, except that the low-temperature annealing temperature is 300° C. and the annealing time is 6 hours.
[0088] Example 10 This embodiment is basically the same as Embodiment 1, except that the high-temperature carbonization temperature is 1500°C.
[0089] Embodiment 11 This embodiment is basically the same as Embodiment 1, except that the mass ratio of asphalt to modifier is 1:2.
[0090] Example 12 This embodiment is basically the same as Embodiment 1, except that the mass ratio of basic zinc carbonate to asphalt is 2:1.
[0091] Embodiment 13 This embodiment is substantially the same as embodiment 7, except that the modifier is calcium gluconate.
[0092] Embodiment 14 This embodiment is substantially the same as embodiment 6, except that the mass ratio of zinc gluconate to zinc acetate is 3:1.
[0093] Embodiment 15 This embodiment is basically the same as Embodiment 8, except that the mass ratio of zinc gluconate, zinc acetate and zinc citrate is 3:1:1.
[0094] Comparative Example 1 The modified raw material of this comparative example is original ultra-high temperature coal tar pitch that has not been formed into carbon microspheres, and the other steps are the same as those in Example 1.
[0095] Comparative Example 2 This comparative example is basically the same as comparative example 1, except that the raw material of this comparative example is high-temperature coal tar.
[0096] Comparative Example 3 The only difference between this comparative example and Example 1 is that the Zn5(OH)6(CO3)2 microspheres are replaced by KCl.
[0097] Comparative Example 4 The only difference between this comparative example and Example 1 is that zinc gluconate, a metal salt modifier, is not added.
[0098] In order to more intuitively demonstrate the performance of the material prepared in the present invention, the following Table 1 lists the main parameters of the samples prepared in the above embodiments and comparative examples.
[0099] At the same time, in order to test the electrochemical properties of the asphalt-based carbon microspheres prepared in the embodiments and comparative examples, the asphalt-based carbon microspheres prepared in the embodiments and comparative examples were used to prepare the negative electrode of the sodium ion battery. The specific preparation method was as follows: the asphalt-based carbon microspheres, conductive carbon black and sodium alginate were ground in a mortar at a mass ratio of 8:1:1, an appropriate amount of ultrapure water was added, and the mixture was ground to a homogeneous phase, transferred to a copper foil, coated on the copper foil using a 100um coater, placed in a vacuum drying oven at 85°C for 12 hours, and prepared into a disc electrode with a diameter of 14 mm using a punching machine to obtain a negative electrode material electrode sheet. The electrode sheets were compacted on a sheet press, and the battery was assembled in a glove box filled with high-purity argon according to the structure of the CR2016 standard button cell, wherein a glass fiber disc with a diameter of 19 mm was used as a diaphragm, a sodium metal sheet with a diameter of 12 mm and a thickness of 0.2 mm was used as a counter electrode and a reference electrode, and 1 mol / L sodium hexafluorophosphate EC-DEC-EMC was used as an electrolyte. After standing for 8 h, the battery was charged and discharged at a current density of 30 mA / g on a blue battery test platform. Figure 3 , Figure 4 .
[0100] Among them, the environmental field emission scanning electron microscope used by Thermo Fisher Scientific's Feso electron microscope can work in a relatively humid or low vacuum environment, so that the sample can maintain its original state in the scanning electron microscope, avoiding deformation, cracking and other problems caused by drying or vacuum treatment. SEM scans the surface of the sample by transmitting an electron beam, and uses the principles of electron reflection, transmission, and scattering to obtain information such as the sample's morphology, structure, and element distribution, and can display these details at a high resolution (level). Figure 1 .
[0101] The specific surface area and pore size analysis was performed using the ASAP-2460 specific surface area and porosity analyzer from Micromeritics Instruments. The specific surface area and pore size analysis can also be used to evaluate the morphology, size distribution, lattice defects and other information. Figure 2 .
[0102] The electrochemical performance test results of the pitch-based hard carbon negative electrode materials corresponding to the samples of each embodiment and comparative example are shown in Table 1.
[0103] Table 1 Main parameters and electrochemical performance test results of some samples in the examples and comparative examples
[0104] By comparing Examples 1, 2, and 3, it can be seen that by changing the concentration of zinc nitrate hexahydrate and the mass ratio of asphalt to template, the specific surface area of the prepared asphalt-based carbon microspheres changes significantly. It can be concluded that increasing the concentration of zinc nitrate hexahydrate solution makes the microsphere template formed more perfect, and the basic zinc carbonate template formed by 0.2M zinc nitrate hexahydrate solution is the best. From the data in the table, it can be seen that under the ratio of 2.0 g Zn5(OH)6(CO3)2 microspheres and 0.4 g CTP, the prepared asphalt-based carbon microspheres have a high specific surface area and rich pore structure, and the electrochemical performance is optimal.
[0105] By comparing Examples 1, 4, 5, 7 and Example 13, it can be seen that when a metal modifier is added, zinc gluconate, zinc citrate, zinc acetate, magnesium gluconate and calcium gluconate modifiers are compared, and zinc gluconate has the best performance among zinc salts as modifiers; by comparing different metal salt modifiers, it can be seen that the product performances of different metal salt modifiers are significantly different, and among zinc salts, magnesium salts and calcium salts, zinc salts have better performance as modifiers.
[0106] By comparing Example 6 and Example 8 as well as Examples 14 and 15, it can be seen that when two or three metal modifiers are added, the electrochemical performance is significantly different under different schemes. The sample with zinc gluconate, zinc acetate and zinc citrate (mass ratio 1:1:1) as modifiers has the best electrochemical performance, but the combined action of the three modifiers will lead to an extreme increase in surface defects, resulting in irreversible consumption of the electrolyte during the charge and discharge process of the battery, resulting in a decrease in the initial efficiency.
[0107] According to the results of Examples 1, 9 and 10, the low-temperature annealing temperature should be less than 500°C, and the high-temperature carbonization temperature is optimal at 1200°C.
[0108] By comparing Example 1 with Comparative Example 1, it can be seen that the carbon microspheres formed by the template method effectively increase the specific surface area of the material and enrich the surface structure, thereby effectively improving the electrochemical performance, compared with the unspheroidized samples.
[0109] According to the results of Comparative Examples 1 and 2, the higher the softening point of the original asphalt is, the higher the electrochemical performance of the prepared negative electrode material is.
[0110] Comparative Example 1 and Comparative Example 3 show that the asphalt-based hard carbon microspheres prepared using Zn5(OH)6(CO3)2 microspheres as templates have better performance than those prepared using KCl templates. This is because the Zn5(OH)6(CO3)2 template not only acts as a template during the pyrolysis process, but also produces oxidizing gases that prevent the material from graphitizing. The small gas molecules produced make the surface of the prepared hard carbon material have a rich closed-pore structure, making the material performance better.
[0111] Comparative Example 1 and Comparative Example 4 show that the electrochemical performance of the asphalt-based hard carbon microspheres obtained after the introduction of metal salt modifiers is better than that without the use of metal salt modifiers. This is because the metal salt modifiers are pyrolyzed to produce gaseous carbon oxides and solid products (ZnO nanoparticles). Gaseous carbon oxides consume excess hydrogen to prevent the orderly arrangement of the carbon skeleton. The solid product expands the interlayer spacing, and finally after removing the ZnO nanoparticles, a large number of closed pores are introduced into the carbon material. The composite modification effect improves the electrochemical performance of the material.
[0112] Figure 1 This is a scanning electron micrograph of the pitch-based carbon microspheres modified with zinc gluconate prepared in Example 1. Figure 1 It can be seen that its surface presents a uniform porous structure.
[0113] Figure 2 The nitrogen adsorption curve of the zinc gluconate-modified asphalt-based carbon microspheres prepared in Example 1 has a specific surface area of 1406 m 2 / g, and the nitrogen adsorption-desorption curve presents a type IV curve, proving that the material has rich microporous structure.
[0114] Figure 3 The initial charge-discharge curves of the modified pitch-based carbon microspheres prepared in Examples 1, 4, and 5 as the negative electrode of sodium ion batteries. It can be seen that zinc gluconate modification is better than other metal salts, and the reversible specific capacity can reach 301 mAh g -1 .
[0115] Figure 4 The efficiency diagram of the modified pitch-based carbon microspheres prepared in Examples 1, 4, and 5 as the negative electrode of sodium ion batteries. It can be seen that the zinc gluconate modification is better than other metal salts, and the initial coulombic efficiency can reach 93.07%.
[0116] In summary, the synthesis of basic zinc carbonate microsphere templates by hydrothermal method, and then heating, stirring and drying with asphalt in a specific solvent to obtain asphalt-based carbon microspheres has a great influence on the specific surface area and pore structure of the material, which in turn affects the electrochemical performance of such negative electrode materials. Specifically: the synthesis of basic zinc carbonate microsphere templates by hydrothermal method, and then heating, stirring and drying with asphalt with different softening points in a specific solvent to obtain asphalt-based carbon microspheres, followed by low-temperature annealing with metal salts such as zinc gluconate, and then high-temperature carbonization, acid washing, water washing and drying to obtain metal salt-modified asphalt-based hard carbon microspheres. The obtained asphalt microspheres have a high specific surface area and rich pore structure. Finally, the ordered arrangement of asphalt molecules at high temperature and the formation of closed pores are changed by modification with metal salts, thereby obtaining hard carbon materials. The hard carbon material obtained by this method has excellent performance, high discharge capacity and first charge and discharge efficiency, good large current charge and discharge performance, and good cycle performance.
[0117] In the present application, the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0118] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0119] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in the field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A method for preparing pitch-based hard carbon microspheres, characterized in that: The following steps are involved: S1, stirring asphalt and basic zinc carbonate microspheres in a solvent to react, and drying the obtained solid product to obtain an asphalt-based carbon microsphere precursor; S2, mixing the asphalt-based carbon microsphere precursor with a metal salt modifier to obtain a modified asphalt-based carbon microsphere precursor; the metal salt modifier is a zinc salt, a magnesium salt or a calcium salt; S3, annealing and carbonizing the modified pitch-based carbon microsphere precursor; S4, acid-washing, water-washing and drying the carbonized product to obtain asphalt-based hard carbon microspheres.
2. The method for preparing pitch-based hard carbon microspheres according to claim 1, characterized in that: In S1, the preparation method of the basic zinc carbonate microspheres is: adding zinc nitrate hexahydrate and urea to water to carry out a hydrothermal reaction, and washing and drying the product to obtain basic zinc carbonate microspheres.
3. The method for preparing pitch-based hard carbon microspheres according to claim 1, characterized in that: S1 specifically comprises: adding asphalt and basic zinc carbonate microspheres into a solvent, stirring at room temperature, and then separating the solid and the liquid, and drying the solid product to obtain a asphalt-based carbon microsphere precursor.
4. The method for preparing pitch-based hard carbon microspheres according to claim 1, characterized in that: In S1, the mass ratio of basic zinc carbonate microspheres to asphalt is (1-10):
1.
5. The method for preparing pitch-based hard carbon microspheres according to claim 1, characterized in that: In S2, the zinc salt is one or more of zinc propionate, zinc gluconate, zinc acetate, zinc oxalate, zinc citrate, zinc lactate, zinc phytate, zinc formate, zinc sulfate, zinc octanoate, zinc isooctanoate and zinc laurate; the magnesium salt is one or more of magnesium propionate, magnesium gluconate, magnesium acetate, magnesium oxalate, magnesium citrate, magnesium lactate, magnesium phytate, magnesium formate, magnesium sulfate, magnesium octanoate, magnesium isooctanoate and magnesium laurate; the calcium salt is one or more of calcium propionate, calcium gluconate, calcium acetate, calcium oxalate, calcium citrate, calcium lactate, calcium phytate, calcium formate, calcium sulfate, calcium octanoate, calcium isooctanoate and calcium laurate.
6. The method for preparing pitch-based hard carbon microspheres according to claim 1, characterized in that: In S2, the ratio of the asphalt-based carbon microsphere precursor to the metal salt modifier is 1:(1-5).
7. The method for preparing pitch-based hard carbon microspheres according to claim 1, characterized in that: In S3, the annealing temperature is 100 to 500° C., and the annealing time is 1 to 12 hours.
8. The method for preparing pitch-based hard carbon microspheres according to claim 1, characterized in that: In S3, the carbonization temperature is 800-1600°C, and the carbonization time is 1-12 hours.
9. Pitch-based hard carbon microspheres obtained by the preparation method according to any one of claims 1 to 8.
10. A sodium ion battery, characterized in that: It comprises a negative electrode, wherein the negative electrode comprises the pitch-based hard carbon microspheres according to claim 9.
Citation Information
Patent Citations
Porous carbon nanomaterial and preparation method thereof
CN113277509A
Porous hard carbon material as well as preparation method and application thereof
CN113735095A
Method for preparing porous carbon material in air atmosphere by utilizing flame-retardant principle
CN114380288A
Preparation method of hollow hydrangea-shaped zinc oxide and product and application of hollow hydrangea-shaped zinc oxide
CN115159560A
Preparation method of high-capacity asphalt-based hard carbon sodium ion battery negative electrode material
CN116969442A
Cited By
Preparation method of spherical pitch-based hard carbon and sodium ion battery
CN120463195A
Asphalt-based hard carbon negative electrode material and preparation method and application thereof
CN120903472A